Women directors and firm innovation: The role of women directors' representative function - Jasmin Joecks; Kerstin Pull; Katrin Scharfenkamp (Managerial and Decision Economics, 2022)
We argue that the link between women directors in co-determined supervisory boards and firm innovation depends on two contextual factors: (1) Women directors' power, as measured by their share among shareholder representatives, and (2) on whether women are represented in both representative functions, that is, shareholder and employee representatives. In our empirical analysis based on German panel data, we find the positive link between women directors and firm innovation to be driven by women shareholder representatives, and we find the joint presence of women among shareholder and employee representatives to be positively linked to firm innovation.
Keywords: 650